Enhancing the Dendrite Tolerance of NaSICON Electrolytes by Suppressing Edge Growth of Na Electrode along Ceramic Surface (Adv. Energy Mater. 40/2022). Issue 40 (27th October 2022) - Ma, Qianli; Ortmann, Till; Yang, Aikai; Sebold, Doris; Burkhardt, Simon; Rohnke, Marcus; Tietz, Frank; Fattakhova‐Rohlfing, Dina; Janek, Jürgen; Guillon, Olivier
Abstract : Solid‐State Batteries In article number 2201680, Qianli Ma and co‐workers discussed the peculiar dendrite‐growth of sodium metal on NaSICON solid‐electrolyte, which occurs along the surface of NaSICON rather than through the solid‐electrolyte. The triple‐phase boundary of the sodium metal, surface‐near Na3.4 Zr2 Si2.4 P0.6 O12 grain‐boundaries and gas phase may be the active domains for the dendrite‐formation. By blocking the surface‐dendrite with a NaNO3 ‐coating, the dendrite‐tolerance of NaSICON is further enhanced.